Computer experiments on the Khirbet Qeiyafa ostracon. - Levy, Eythan; Pluquet, Frédéric (Digital Scholarship in the Humanities, 2017)
This article presents a new theoretical framework for computer-assisted decipherment of ancient alphabetic inscriptions. This framework is based on regular expressions, a widely used computer science formalism for encoding text strings with partially unknown characters. We then present a new software called SCRYPT, which applies our framework to the Khirbet Qeiyafa ostracon, an important Proto-Canaanite inscription recently discovered in Israel, as a first case study. Several new anthroponymic readings for the Qeiyafa ostracon, found with the help of our software, are presented as part of that case study. The software, freely available online (www.ScryptApp.com), enables users to encode all possible readings for a given grapheme in the ostracon and provides fast automated dictionary searches for lexemes.